Efficiency of Paecilomyces variotii in Bioremoval of Reactive Black Dye from Tannery Effluent - Priya Chokkalingam, Mahi Anamalagundam, Chaithanya Lahari, Shreya Singh, G. Mohan Kumar and Rajeswary Hari (Nature Environment and Pollution Technology, 2023)
The present work investigates the efficiency of Paecilomyces variotii upon degrading Reactive Black dye which has been termed a recalcitrant variety of synthetic dye. In this research, initially a predominant fungal species, Paecilomyces variotii was isolated from the tannery effluent sample. The study was carried out by assessing the ability of fungi to decolorize the dye under various parameters like pH (5,7 and 9), Temperature (7°C, 30°C, and 45°C), Dye concentration (200, 300, and 400 mg/L) for different incubation or exposure time interval (3, 5 and 7 days). From the experimental study, it was found that Paecilomyces variotii showed a maximum percentage of dye decolorization at 7°C at pH 9 with 75%, at 30°C at pH 7 with 85%, at 45°C at pH 5 with 82% and a maximum period of incubation with 7 days in 200 mg.L-1 concentration. This result conveys that the strength of Paecilomyces variotii in decolorizing the synthetic dye is effective at a moderate temperature with neutral pH for maximum exposure time. So Paecilomyces variotii could be a good candidate of choice for the biodegradation of various synthetic dyes when manipulated wisely. Also, the result sparks a positive attribute toward decreasing industrial wastewater pollution.